PERTANGGUNGJAWABAN PIDANA PEJABAT PEMBUAT AKTA TANAH (PPAT) SEBAGAI PELAKU TINDAK PIDANA PENGGELAPAN (ANALISIS PUTUSAN PN BALIKPAPAN NOMOR 685/PID.SUS/2019/PN.BPP) - Dita Tisnadewi, Made; Lumban Gaol, Selamat (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
A PPAT receiving the certificate may not use the entrusted certificate for personal interests. It can be interpreted that the certificate is a State document which is in the custody of the Notary/PPAT office. In connection with this authority, PPAT can be burdened with responsibility for actions that are not in accordance with applicable regulations or are carried out unlawfully. Therefore, it is very interesting and important to study further how the crime of embezzlement is regulated in Indonesian criminal law? and what are the legal considerations of the panel of judges in the Balikpapan District Court decision Number 685/PID.SUS/2019/PN.BPP regarding the criminal liability of Land Deed Officials (PPAT) as perpetrators of the crime of embezzlement? To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that the criminal act of embezzlement has been regulated in Article 372 of the Criminal Code and Article 486 of Law 1/2023 concerning the new Criminal Code which is valid for 3 years from the date of promulgation, namely 2026. Based on decision number 685/PID.SUS/2019/PNBPP, this is true. committing unlawful acts based on the provisions of Article 372 of the Criminal Code. PPAT (defendant) fulfills the elements, namely the element of who; intentionally and unlawfully; owning an item in whole or in part; the goods are in his control, not because of someone else's crime. The PPAT (defendant) must be held accountable for the crime in prison for a maximum of 4 years.